Servo prevalence of hepatitis B and C and HIV in multiple transfusions ß-thalassemia: Result from an only thalassemia day care unit in Kerman-Iran - Amir-Hooshang Sheikh-Bardsiri; Amin-Reza Owhadi; Andre M.N. Renzaho; Maryam Delavari (Mediterranean Journal of Hematology and Infectious Diseases)
Patients with major ß-thalassemia require multi-transfusions for survival. They are at a high risk for blood transfusion transmitted infections, particularly with Hepatitis B virus (HBV), Hepatitis C virus (HCV) and Human immunodeficiency virus (HIV). The aim of this study was to evaluate the prevalence of HBV, HCV and HIV infection in ß-thalassemic patients in Kerman province, Iran. Serum samples were collected from 197 patients with major ß-thalassemia from an only thalassemic day care unit in Kerman province during 1 year. Using the Enzyme-linked immunosorbent assay, four different blood tests were performed: hepatitis B surface antigen and anti HBs-Ab for Hepatitis B, anti-HCV for Hepatitis C and anti-HIV antibody for HIV. None of the subjects were positive for anti-HIV antibody, while the prevalence of HBs-Ag, anti-HBs and anti-HCV antibodies were observed in 2%, 33%, and 28.4% of the patients, respectively. Age and duration of the disease had independent significant effect on the prevalence of HCV positivity. Despite the observed low prevalence of hepatitis C virus positivity in pre transfusion screening of donated bloods, a significant prevalence of HCV positivity has been discovered among patients with major ß-thalassemia. A more reliable screening test of HCV in Iran Blood Bank should be integrated.